2015
DOI: 10.35691/jbm.5102.0029
|View full text |Cite
|
Sign up to set email alerts
|

Naphthalene Acetic Acid and Benzylaminopurine Enhance Growth and Improve Quality of Organic Spinach in Kitchen Gardens

Abstract: The present study was conducted at the Kitchen Gardening Training Centre, Faisalabad, Pakistan to evaluate the effect of the plant growth regulators Naphthalene Acetic Acid (NAA) and Benzylaminopurine (BAP), on the growth and yield of organic spinach (Spinacia oleracea L.) in kitchen gardening. Different combinations and concentrations of NAA and BAP were tested to evaluate different vegetative parameters. The data were recorded at 40 and 60 days after sowing (DAS). Maximum plant height at 40 DAS was recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Pahare and Das (2020) reported that the plant height of periwinkles increased in response to the application of NAA. Awan et al (2015) found that the plant height of spinach improved in response to the application of NAA and BA. Pal et al (2016) reported an increase in plant height in cucumber plants following the application of gibberellic acid and potassium.…”
Section: Plant Heightmentioning
confidence: 99%
“…Pahare and Das (2020) reported that the plant height of periwinkles increased in response to the application of NAA. Awan et al (2015) found that the plant height of spinach improved in response to the application of NAA and BA. Pal et al (2016) reported an increase in plant height in cucumber plants following the application of gibberellic acid and potassium.…”
Section: Plant Heightmentioning
confidence: 99%